Investasi Emas Digital Perspektif Shaykh Wahbah Al Zuhayli Dan Fatwa DSN-MUI - Shelvyna Rikantasari; Kholishudin; Muhammad Lathoif Ghozali (Al-Musthofa: Journal of Sharia Economics, 2025)
The legal view on gold savings from the perspective of DSN-MUI and Shaykh Wahbah Zuhayli has basic similarities, namely from the nash hadith, but differs in the legal istinbat on the nas. This research aims to uncover the legal review of gold investment from the perspective of DSN-MUI and Shaykh Wahbah Zuhayli. The research uses qualitative methods and data collection uses documentation techniques to be further analyzed descriptively -critically on the arguments of both parties about gold investment. This research shows the view of MUI that it allows gold investment with istidlal that in the current context gold has changed not as a means of transaction but has been transformed as sil'ah (valuable goods). Meanwhile, according to Wahbah Zuhaili, it is the view that gold savings should not be based on the textual understanding of the hadith because gold is a usury item.